Techniques for vibration control of a flexible robot manipulator - Mohamed, Zaharuddin; Chee, A.K.; Mohd Hashim, A.W.I.; Tokhi, Mohammad Osman; Mohd Amin, Shamsudin; Mamat, Rosbi (Cambridge University Press, 2006)
This paper presents investigations into the applications and performance of positive and negative input shapers in command shaping techniques for the vibration control of a flexible robot manipulator. A constrained planar single-link flexible manipulator is considered and the dynamic model of the system is derived using the finite element method. An unshaped bang-bang torque input is used to determine the characteristic parameters of the system for design and evaluation of the input shaping control techniques. The positive and specified amplitude negative input shapers are designed based on the properties of the system. Simulation results of the response of the manipulator to the shaped inputs are presented in the time and frequency domains. Performances of the shapers are examined in terms of level of vibration reduction, time response specifications and robustness to parameters uncertainty. The effects of derivative order of the input shaper on the performance of the system are investigated. Finally, a comparative assessment of the impact amplitude polarities of the input shapers on the system performance is presented and discussed.